Makna utang dan praktik mental accounting: studi kualitatif terhadap nasabah PT. Pegadaian Syariah di Madura - Sukma, Vega Melati; Juanda, Achmad; Leniwati, Driana (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2025)
This study aims to examine the relationship between debt perception and mental accounting, particularly self-control and time-consistent behavior, within the context of Islamic finance and their influence on preventing non-performing financing (NPF) at PT Pegadaian Syariah in Madura, Indonesia. A qualitative descriptive approach was employed through in-depth interviews, observations, and documentation involving ten purposively selected active customers who had used Islamic financing products for at least six months. Data analysis revealed variations in financial behavior based on gender and age, focusing on debt perception, budgeting strategies, and repayment discipline. The findings show that most customers perceive debt positively as a productive financial tool, a moral responsibility, and a means to enhance business and family welfare. Female customers tend to manage detailed budgets and involve family in financial decisions, while males focus on separating business and personal funds. Older customers (>40 years) exhibit greater repayment discipline. Self-control is reflected in prioritizing installments over discretionary spending, while time-consistent behavior is maintained through fixed schedules and reserve funds. These findings align with Mental Accounting Theory, indicating that effective fund allocation and repayment discipline significantly reduce NPF risk. The study contributes to behavioral finance literature and offers practical insights for Islamic financial institutions in developing targeted financial education programs to promote disciplined budgeting and minimize default risk.